Feasibility study of thermal energy harvesting using lead free pyroelectrics. (7th April 2016) - Karim, Hasanul; Sarker, Md Rashedul H; Shahriar, Shaimum; Shuvo, Mohammad Arif Ishtiaque; Delfin, Diego; Hodges, Deidra; Tseng, Tzu-Liang (Bill); Roberson, David; Love, Norman; Lin, Yirong
Abstract: Energy harvesting has significant potential for applications in energizing wireless sensors and charging energy storage devices. To date, one of the most widely investigated materials for mechanical and thermal energy harvesting is lead zirconate titanate (PZT). However, lead has detrimental effects on the environment and on health. Hence, alternative materials are required for this purpose. In this paper, a lead free material, lithium niobate (LNB) is investigated as a potential material for pyroelectric energy harvesting. Although its theoretical pyroelectric properties are lower compared to PZT, it has better properties than other lead free alternatives such as ZnO. In addition, LNB has a high Curie temperature of about 1142 °C, which makes it applicable for high temperature energy harvesting, where other pyroelectric ceramics are not suitable. Herein, an energy harvesting and storage system composed of a single crystal LNB and a porous carbon-based super-capacitor was investigated. It is found that with controlled heating and cooling, a single wafer of LNB (75 mm diameter and 0.5 mm thickness) could generate 437.72 nW cm –3 of power and it could be used to charge a super-capacitor with a charging rate of 2.63 mV (h cm 3 ) –1 .